2018
DOI: 10.1002/ejoc.201801590
|View full text |Cite
|
Sign up to set email alerts
|

Ethynyl‐Tolyl Extended 2‐(2′‐Hydroxyphenyl)benzoxazole Dyes: Solution and Solid‐state Excited‐State Intramolecular Proton Transfer (ESIPT) Emitters

Abstract: Dual solution/solid‐state emissive fluorophores based on a 2‐(2′‐Hydroxyphenyl)benzoxazole (HBO) core bearing one or two ethynyl‐tolyl moieties at different positions were synthesized via an expedite two‐step synthetic procedure. HBO derivatives are known to display intense Excited‐State Intramolecular Proton Transfer (ESIPT) emission in the solid‐state but are mildly emissive in solution due to the detrimental flexibility of the excited‐state opening efficient non‐radiative pathways. The sole introduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…However, for dyes 2 , 3 , and 6 , the substitution by p - N , N ,-diethylaniline (NEt 2 ) groups leads to a dual E*/K* emission at 476/599, 470/565, and 475/603 nm, respectively. These observations indicate that the electrodonating characteristic of the NEt 2 group contributes to the stabilization of the energy level of E*, leading to a partial frustration of the proton transfer, which is a typical feature in such systems. ,, It is a clear indication that electron donors tend to decrease the acidity of the phenolic proton in the excited state (i.e., decrease of p K a *), leading to dual emission. Also, it is worth noting that this dual emission is observed in apolar toluene, highlighting the fact that ESIPT frustration is exclusively due to the electronic parameters and not the solvation effect in the protic environment.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…However, for dyes 2 , 3 , and 6 , the substitution by p - N , N ,-diethylaniline (NEt 2 ) groups leads to a dual E*/K* emission at 476/599, 470/565, and 475/603 nm, respectively. These observations indicate that the electrodonating characteristic of the NEt 2 group contributes to the stabilization of the energy level of E*, leading to a partial frustration of the proton transfer, which is a typical feature in such systems. ,, It is a clear indication that electron donors tend to decrease the acidity of the phenolic proton in the excited state (i.e., decrease of p K a *), leading to dual emission. Also, it is worth noting that this dual emission is observed in apolar toluene, highlighting the fact that ESIPT frustration is exclusively due to the electronic parameters and not the solvation effect in the protic environment.…”
Section: Resultsmentioning
confidence: 59%
“…In the neutral state, the pyridine moiety favors complete deprotonation of the excited phenol, leading to the impossibility of ESIPT to occur and the emission of the resulting phenolate. Indeed, it is reported that the phenolate moieties derived from HBO dyes can be highly emissive. , Moreover, the formation of the phenolate in neutral dichloromethane is consistent with the ab initio calculations (see below). To further evidence deprotonation in the excited state, the absorption and emission spectra of dye 8 in the presence of 0.1% base (NEt 3 ) were recorded, leading to similar maximum wavelengths (λ abs /λ em = 333/498 nm) as in neutral dichloromethane (Figure S75).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…Generally, their photophysical properties can be easily modulated using many strategies [2,3] such as introducing electron-donating and withdrawing substituents, the heteroatom substitution, and the π-conjugation into the main core structure, to give the desirable absorption and emission spectra as well as large Stokes shift. The ESIntraPT molecules with such tunable photophysical properties including derivatives of salicylates [4][5][6], salicylideneanilines [7][8][9], flavones [10][11][12][13], benzazoles [14][15][16][17][18], and chalcones [19][20][21] have been reported and widely used in various applications ranging from chemical sensing to light-emitting diodes [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%